Small-scale variability in Arctic zooplankton around Southampton Island, Nunavut - Andrea Niemi; C-Jae Breiter; Sławomir Kwaśniewski; Mateusz Ormańczyk; Alexis Burt; Jens Ehn; Elizabeth Kitching; Jessica Mai; C. J. Mundy (Polar Biology, 2026)
Polynyas, tidal straits, and variable water column structure support diverse and productive habitats around Southampton Island, northern Hudson Bay, Nunavut, Canada. This study provides the first description of zooplankton at depths between 18 and 313 m around the island, including pelagic larval stages of benthic invertebrates (i.e., meroplankton). From the stations sampled in August 2018 and 2019, 83 taxa were identified with an average station species richness of 27. Bivalve larvae were present at all stations and were the most abundant meroplankton taxa. A distinct Northern and Southern zooplankton assemblage was identified. Average total zooplankton abundance was 5.4 times higher at Northern stations in Frozen Strait, and at stations adjacent to Foxe Basin and Foxe Channel, relative to Southern stations. The Northern assemblage was numerically dominated by calanoid copepods whereas the Southern assemblage had higher abundances of cyclopoid copepods including Oithona similis . Metridia longa and Oikopleura spp. were strong indicator taxa of the Northern assemblage, in contrast to hydrozoans (i.e., Aglantha digitale and Aeginopsis laurentii ) and the nauplii of euphausiids for the Southern assemblage. This study also documented a transient coastal assemblage caused by a wind event that decreased zooplankton abundance and biomass by an order of magnitude in Fisher Strait. The zooplankton around Southampton Island reflect small-scale variability at the intersection of sub-Arctic and Arctic regions with limited estuarine influence, resulting in summer assemblages distinct from southern or western coastal Hudson Bay and nearby waters of Hudson Strait or central Hudson Bay.

Correction to: A stakeholder-guided marine heatwave hazard index for fisheries and aquaculture - Jules B. Kajtar; Neil J. Holbrook; Anna Lyth; Alistair J. Hobday; Craig N. Mundy; Sarah C. Ugalde (Climatic Change, 2024)

A stakeholder-guided marine heatwave hazard index for fisheries and aquaculture - Jules B. Kajtar; Neil J. Holbrook; Anna Lyth; Alistair J. Hobday; Craig N. Mundy; Sarah C. Ugalde (Climatic Change, 2024)
Marine heatwaves pose an increasing threat to fisheries and aquaculture around the world under climate change. However, the threat has not been estimated for the coming decades in a form that meets the needs of these industries. Tasmanian fisheries and aquaculture in southeast Australia have been severely impacted by marine heatwaves in recent years, especially the oyster, abalone, and salmon industries. In a series of semi-structured interviews with key Tasmanian fishery and aquaculture stakeholders, information was gathered about the following: (i) the impacts they have experienced to date from marine heatwaves, (ii) their planning for future marine heatwaves, and (iii) the information that would be most useful to aid planning. Using CMIP6 historical and future simulations of sea surface temperatures around Tasmania, we developed a marine heatwave hazard index guided by these stakeholder conversations. The region experienced a severe marine heatwave during the austral summer of 2015/16, which has been used here as a reference point to define the index. Our marine heatwave hazard index shows that conditions like those experienced in 2015/16 are projected to occur approximately 1-in-5 years by the 2050s under a low emissions scenario (SSP1-2.6) or 1-in-2 years under a high emissions scenario (SSP5-8.5). Increased frequency of marine heatwaves will likely reduce productivity by both direct (mortality) and in-direct (ecosystem change, greater incidence of disease) impacts on target species. The illustrative hazard index is one step towards a marine heatwave risk index, which would also need to consider aspects of exposure and vulnerability to be of greater utility to stakeholders.

Cusk-eel confusion: revisions of larval Luciobrotula and Pycnocraspedum and re-descriptions of two bythitid larvae (Ophidiiformes) - Matthew G. Girard; Bruce C. Mundy; Ai Nonaka; G. David Johnson (Ichthyological Research, 2023)

Hexahydro-1,3,5-trinitro-1,3,5-triazine (RDX) causes seizure activity in larval zebrafish via antagonism of γ-aminobutyric acid type A receptor α1β2γ2 - Paige C. Mundy; Alicia Werner; Latika Singh; Vikrant Singh; Rosalia Mendieta; Caitlyn E. Patullo; Heike Wulff; Pamela J. Lein (Archives of Toxicology, 2023)
Hexahydro-1,3,5-trinitro-1,3,5-triazine, or Royal Demolition Explosive (RDX), is a major component of plastic explosives such as C-4. Acute exposures from intentional or accidental ingestion are a documented clinical concern, especially among young male U.S. service members in the armed forces. When ingested in large enough quantity, RDX causes tonic–clonic seizures. Previous in silico and in vitro experiments predict that RDX causes seizures by inhibiting α1β2γ2 γ-aminobutyric acid type A ( GABA A ) receptor-mediated chloride currents. To determine whether this mechanism translates in vivo, we established a larval zebrafish model of RDX-induced seizures. After a 3 h of exposure to 300 µM RDX, larval zebrafish exhibited a significant increase in motility in comparison to vehicle controls. Researchers blinded to experimental group manually scored a 20-min segment of video starting at 3.5 h post-exposure and found significant seizure behavior that correlated with automated seizure scores. Midazolam (MDZ), an nonselective GABA A R positive allosteric modulator (PAM), and a combination of Zolpidem (α1 selective PAM) and compound 2-261 (β2/3-selective PAM) were effective in mitigating RDX-triggered behavioral and electrographic seizures. These findings confirm that RDX induces seizure activity via inhibition of the α1β2γ2 GABA A R and support the use of GABA A R-targeted anti-seizure drugs for the treatment of RDX-induced seizures.

Monitoring a changing Arctic: Recent advancements in the study of sea ice microbial communities - Karley Campbell; Ilkka Matero; Christopher Bellas; Thomas Turpin-Jelfs; Philipp Anhaus; Martin Graeve; Francois Fripiat; Martyn Tranter; Jack Christopher Landy; Patricia Sanchez-Baracaldo; Eva Leu; Christian Katlein; et al. (Ambio, 2022)
Sea ice continues to decline across many regions of the Arctic, with remaining ice becoming increasingly younger and more dynamic. These changes alter the habitats of microbial life that live within the sea ice, which support healthy functioning of the marine ecosystem and provision of resources for human-consumption, in addition to influencing biogeochemical cycles (e.g. air–sea CO 2 exchange). With the susceptibility of sea ice ecosystems to climate change, there is a pressing need to fill knowledge gaps surrounding sea ice habitats and their microbial communities. Of fundamental importance to this goal is the development of new methodologies that permit effective study of them. Based on outcomes from the DiatomARCTIC project, this paper integrates existing knowledge with case studies to provide insight on how to best document sea ice microbial communities, which contributes to the sustainable use and protection of Arctic marine and coastal ecosystems in a time of environmental change.

Descriptions and records of liparid fishes (Scorpaeniformes, Liparidae) from the Mariana Islands - David L. Stein; Bruce C. Mundy (Ichthyological Research, 2022)

Seasonal dynamics of algal and bacterial communities in Arctic sea ice under variable snow cover - K. Campbell; C. J. Mundy; C. Belzile; A. Delaforge; S. Rysgaard (Polar Biology, 2018)

Primate genotyping via high resolution melt analysis: rapid and reliable identification of color vision status in wild lemurs - Rachel L. Jacobs; Amanda N. Spriggs; Tammie S. MacFie; Andrea L. Baden; Mitchell T. Irwin; Patricia C. Wright; Edward E. Louis; Richard R. Lawler; Nicholas I. Mundy; Brenda J. Bradley (Primates, 2016)

Consequences of change and variability in sea ice on marine ecosystem and biogeochemical processes during the 2007–2008 Canadian International Polar Year program - David G. Barber; Matthew G. Asplin; Tim N. Papakyriakou; Lisa Miller; Brent G. T. Else; John Iacozza; C. J. Mundy; M. Gosslin; Natalie C. Asselin; Steve Ferguson; Jennifer V. Lukovich; Gary A. Stern; et al. (Climatic Change, 2012)

Spatial and temporal variation of photosynthetic parameters in natural phytoplankton assemblages in the Beaufort Sea, Canadian Arctic - Molly A. Palmer; Kevin R. Arrigo; C. J. Mundy; Jens K. Ehn; Michel Gosselin; David G. Barber; Johannie Martin; Eva Alou; Suzanne Roy; Jean-Éric Tremblay (Polar Biology, 2011)

Characteristics of two distinct high-light acclimated algal communities during advanced stages of sea ice melt - C. J. Mundy; Michel Gosselin; Jens K. Ehn; Claude Belzile; Michel Poulin; Eva Alou; Suzanne Roy; Haakon Hop; Sylvie Lessard; Tim N. Papakyriakou; David G. Barber; Jeremy Stewart (Polar Biology, 2011)

Two deep-sea spiny eels, Notacanthus abbotti and Lipogenys gillii (Albuliformes: Notacanthidae), from the Hawaiian Archipelago and Emperor Seamounts with notes on their identification and biogeography - Bruce C. Mundy; Kathleen Cole; E. H. Chave; Robert B. Moffitt (Ichthyological Research, 2011)

The Prevalence of Fentanyl in Drug-Related Deaths in Philadelphia 2004–2006 - Stella C. Wong; Lisa Mundy; Rebecca Drake; John A. Curtis; William E. Wingert (Journal of Medical Toxicology, 2010)

Linking ice structure and microscale variability of algal biomass in Arctic first-year sea ice using an in situ photographic technique - C. J. Mundy; D. G. Barber; C. Michel; R. F. Marsden (Polar Biology, 2007)

Notes on the morphology of the early stage of the rare bramid genus Eumegistus - Masato Moteki; Bruce C. Mundy (Ichthyological Research, 2005)

In situ fertilisation success in the scleractinian coral Goniastrea favulus - K. J. Miller; C. N. Mundy (Coral Reefs, 2005)

Factors Affecting Group Spread within Wild Mixed-Species Troops of Saddleback and Mustached Tamarins - Andrew C. Smith; Hannah M. Buchanan-Smith; Alison K. Surridge; Nicholas I. Mundy (International Journal of Primatology, 2005)

Rapid settlement in broadcast spawning corals: implications for larval dispersal - K. Miller; C. Mundy (Coral Reefs, 2003)

Caleosins: Ca2+-binding proteins associated with lipid bodies - Henrik Næsted; Gitte I. Frandsen; Guang-Yuh Jauh; Immaculada Hernandez-Pinzon; Henrik B. Nielsen; Denis J. Murphy; John C. Rogers; John Mundy (Plant Molecular Biology, 2000)

An appraisal of methods used in coral recruitment studies - C. N. Mundy (Coral Reefs, 2000)

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)

Quantitative structure activity study of a series of substituted 0,0-dimethyl 0-(p-nitrophenyl) phosphorothioates and 0-analogs - R. L. Mundy; M. C. Bowman; J. H. Farmer; T. J. Haley (Archives of Toxicology, 1978)